2017
DOI: 10.1002/cphc.201700629
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Density Functionals for Computing Thermodynamic Properties of Lanthanide Complexes

Abstract: The equilibrium between the radical phenanthroline complex Cp*2Sm(phen) and the coupling product (Cp*2Sm(phen))2 has been investigated based on quantum chemistry calculations. Topological analyses pointed out that the C−C bond created has a partial covalent character, explaining why both the monomeric and the dimeric forms exist in equilibrium. A large variety of density functionals have been tested to reproduce experimental thermodynamic data for this equilibrium. Finally, the PBE0‐D3 and M06‐2X functionals l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…Density functional theory (DFT) has been extensively applied to estimate thermodynamic properties of TM complexes. 4,5 However, the DFT based prediction workflows commonly face major challenges with respect to the accuracy of the calculations (basis set; XC functional; solvation model) and the computational costs. The method accuracy in DFT towards prediction of thermochemical properties can be addressed by validation against the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) has been extensively applied to estimate thermodynamic properties of TM complexes. 4,5 However, the DFT based prediction workflows commonly face major challenges with respect to the accuracy of the calculations (basis set; XC functional; solvation model) and the computational costs. The method accuracy in DFT towards prediction of thermochemical properties can be addressed by validation against the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] In particular, Kagan reported the reaction of ketones for the preparation of alcohols or pinacols, depending upon the reaction conditions. 26 After some of us demonstrated that this typical radical coupling induced by divalent lanthanides was reversible in multiple cases, [27][28][29][30] we were interested in investigating the Kagan reaction with benzophenone and SmI 2 in THF. The reaction with 1 eq.…”
mentioning
confidence: 99%
“…Following the recent investigations on the coordination compounds and lanthanide complexes, we applied density functional theory (DFT) and its time‐dependent extension (TD‐DFT) and employing the range‐separated hybrid functional ωB97X‐3D that includes empirical corrections for long range non‐bonded dispersive interactions (parametrized DF including 100% long‐range exact exchange) and basis set DEF2‐SVP . This is one of the recommended methods for geometries including molecules incorporating transition metals .…”
Section: Methodsmentioning
confidence: 99%
“…We developed a sensitive method for the determination of NAL and other similar drugs based on luminescence quenching of TbCCE probe . The research field of lanthanide complexes is of great interest today Luminescent photoprobes of lanthanide complexes are more advantageous than traditionally. used ones; due to its high stability and durability …”
Section: Introductionmentioning
confidence: 99%